Voltage controller of a micro boost converter for rain water harvesting system - Mohammad Amaluddin Mansor, 1992-, author; Norzanah Rosmin, supervisor; Fakulti Kejuruteraan Elektrik (2016)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2016